GE_GERICHTE C/12059/2016 vom 13. Februar 2017 - GE Cour de justice (2017)
OPPOSITION(PROCÉDURE); ORDONNANCE DE SÉQUESTRE ; GAGE ; DROIT ÉTRANGER ; PREUVE ILLICITE | LP.271; LP.37; LDIP.16; CC.2; CPC.152; LP.273;